2007
DOI: 10.3758/bf03193484
|View full text |Cite
|
Sign up to set email alerts
|

The validity of “conceptual span” as a measure of working memory capacity

Abstract: Three experiments tested whether a modified version of the Clustered Conceptual Span task (H. J. Haarmann, E. J. Davelaar, & M. Usher, 2003), which ostensibly requires active maintenance of semantic representations, predicted individual differences in higher-order cognitive abilities better than short-term memory (STM) span tasks or nonsemantic versions of the "Conceptual" task did. Nonsemantic Conceptual tasks presented short word lists clustered by color, first letter, or initial vowel sound, and cued subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 38 publications
0
18
0
Order By: Relevance
“…Moreover, as we opted for the use of mostly standardized and often used memory tasks, the involvement of control processes may differ across them. Specifically, whereas the contribution of control processes is likely to be minimal in the phonological storage task (forward digit span), the semantic storage task (conceptual span) might involve some updating of information (see also Kane & Miyake, 2007). Together, this warrants caution in the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, as we opted for the use of mostly standardized and often used memory tasks, the involvement of control processes may differ across them. Specifically, whereas the contribution of control processes is likely to be minimal in the phonological storage task (forward digit span), the semantic storage task (conceptual span) might involve some updating of information (see also Kane & Miyake, 2007). Together, this warrants caution in the interpretation of the results.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, whereas the contribution of control processes is likely to be minimal in the phonological storage task (e.g., forward digit span task), the semantic storage task (e.g., conceptual span task) might involve some updating of information as in WM, and perhaps especially so for the Non-Clustered version of the task (see also [33]). For example, using a Non-Clustered version of the Conceptual Span task, Haarmann, Ashling, Davelaar, and Usher [15] found that semantic STM predicted successful performance on a widely-used measure of cognitive control: the AX-Continuous Performance Task [34].…”
Section: Introductionmentioning
confidence: 99%
“…Haarmann and his colleagues [3] also found that the Conceptual Span task (in the Non-Clustered version) predicted individual differences not only in language processing but also in fluid intelligence, showing an important contribution of semantic STM to higher-order cognitive processes. However, in another study [33], it was observed that when the to-be-remembered words were presented in a clustered fashion, the Conceptual Span task lost its ability to predict intelligence compared to an unclustered version, suggesting that the predictive capacity of the Conceptual Span task depends on the ability to reorganize the information (clustering ability, including WM). Nevertheless, in a later study [14] it was found that both versions of the Conceptual Span task strongly correlated with fluid intelligence, although the Non-Clustered version showed a somewhat higher correlation than the Clustered one ( r (72) = .67, and r (72) = .52, for the Non-Clustered and for the Clustered version, respectively, combining across older and younger adults; r (36) = .55, and r (36) = .22 for younger adults alone; r (36) = .61, and r (36) = .46 for older adults alone.…”
Section: Introductionmentioning
confidence: 99%
“…However, there was a time limit of 10 minutes. Kane & Miyake (2007) reported a reliability of alpha = .76 and a correlation of .59 with the Nelson-Denny comprehension test (no form given). 8…”
Section: New Text Comprehension Testmentioning
confidence: 99%
“…New text comprehension test 3: The final comprehension test was one used by Kane & Miyake (2007). It consisted of 20 short text fragments (40-114 words) ending with a question and five response alternatives.…”
Section: New Text Comprehension Testmentioning
confidence: 99%